Computing the Nash solution for scheduling bargaining problems. (2nd June 2009) - Agnetis, Alessandro; De Pascale, Gianluca; Pranzo, Marco
In this paper we focus on the Nash Bargaining Solution (NBS) in a scheduling scenario with two players. The problem is shown to be NP-hard, but an effective computing scheme for finding NBS is presented. Extensive computational results are provided, showing that NBS can always be found within reasonable computation time.